HARMONY OF THE CHANTING OF KENDURI PRAYERS IN THE SOUND TRADITION OF THE GAYO COMMUNITY: KESELARASAN LANTUNAN DOA KENDURI DALAM TRADISI BUNYI MASYARAKAT GAYO - DIAN MUHCTAR, ZUHRI ARADIKA; Palawi, Ari; Astuti, Yuli (Jurnal Penelitian Musik, 2025)
This research aims to examine the harmony between prayer chants in the implementation of kenduri and the tradition of musical sounds in the Gayo community. Through an ethnographic approach, this study explores the structure, function and meaning of prayer chants in the context of kenduri, and analyzes how these prayers are harmonized and integrated with traditional Gayo sound elements. The results of the research show that the prayer chants at the Gayo community's kenduri have a unique structure and pattern that is rich in rhythm, intonation and distinctive lyrics. These prayers function as a means to ask for blessings, express gratitude, and confirm the cultural values ​​and beliefs of local communities. The integration of prayer chants and harmonious sounds creates a solemn, serene and sacred atmosphere during the celebration of the kenduri. This reciprocal interaction between prayer and sound also plays an important role in maintaining the continuity and preservation of Gayo cultural traditions. This research provides an in-depth understanding of how spiritual, aesthetic and contextual components interact and influence each other in the cultural practices of the Gayo community. Keywords: prayer chanting, kenduri, musical sound tradition, Gayo society, cultural integration.